Thermally enhanced solid–liquid separation process in food waste biorefinery: modelling the anaerobic digestion of solid residues - Gallipoli, Agata; Angelini, Francesca; Angelini, Stefania; Braguglia, Camilla Maria; Montecchio, Daniele; Tonanzi, Barbara; Gianico, Andrea (Frontiers in Bioengineering and Biotechnology, 2024)
The biochemical valorization potential of food waste (FW) could be exploited by extracting decreasing added-value bio-based products and converting the final residues into energy. In this context, multi-purpose and versatile schemes integrating thermal and biochemical conversion processes will play a key role. An upstream thermal pretreatment + solid-liquid separation unit was here proposed to optimize the conversion of the liquid fraction of FW into valuable chemicals through semi-continuous fermentation process, and the conversion of the residual solid fraction into biomethane through anaerobic digestion.The solid residues obtained after thermal pretreatment presented a higher soluble COD fraction, which resulted in higher methane production with respect to the raw residues (0.33 vs 0.29 Nm 3 CH4 kg -1 VSfed) and higher risk of acidification and failure of methanogenesis when operating at lower HRT (20 d). On the contrary, at HRT = 40 d, the pretreatment did not affect the methane conversion rates and both tests evidenced similar methane productions of 0.33 Nm 3 CH4 kg -1 VSfed. In the reactor fed with pretreated residue, the association of hydrogenotrophic methanogens with syntrophic bacteria prevented the acidification of the system.Modelling proved the eligibility of the FW solid residues as substrates for anaerobic digestion, given their small inert fractions that ranged between 0% and 30% of the total COD content.